Sistem Pakar Deteksi Hemangioma pada Batita menggunakan Metode Hybrid - Firna Yenila; Suci Wahyuni; Eva Rianti; Hari Marfalino; Devi Gusmita (SEULANGA SYSTEM PUBLISHER, 2022)
Hemangioma is a type of disease caused by active glands in the body. Hemangiomas occur in newborns up to the age of five (BATITA). This disease is indicated when a toddler has a fever or body temperature of more than 38°C. This condition affects the nerves and motor organs of the body that are attacked. This condition is sometimes undetected but develops quickly so it is necessary to consult an expert. This study aims to provide building a system in providing early education to parents in identifying toddlers with hemangiomas. This research makes it easy for parents to carry out further consultations with experts regarding the condition of toddlers. The processing of data and facts in this study was carried out by combining several methods (hybrid) in tracing each symptom according to the conditions experienced by system users. This method is continued by giving a weight value in the form of a percentage for each symptom experienced. The results of this study provide new knowledge in the form of information about Hemangioma with a confidence value in the form of a percentage of the patient's condition. This research provides the latest breakthrough in the form of presenting a system using an application that provides an accuracy value to ensure that patients have Hemangioma. This system can provide maximum value for users in gaining new knowledge for patients before further consultation with experts to get action.